Identifikasi Masalah Pada UMKM Kota Padang dan Solusinya Pada Kedai Sala Lauak dan Perkedel Jagung di Depan Kampus UPI ”YPTK” Padang - Mutia Sahilna; Nadia Putri; Neneng Senja Agusta; Nurkhalifah Salsabilla; Vivi Nila Sari (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
Micro, Small and Medium Enterprises (MSMEs) are a form of productive economy that stands alone, meaning that these businesses are not subsidiaries or branches of any company, whether government companies or individual companies. In this research, researchers chose MSMEs located in front of the UPI "YPTK" Padang Campus, namely the Sala Lauak and Corn Perkedel Shop. Currently, the Sala Lauak and corn fritters shop in front of the UPI "YPTK" Padang campus is still experiencing problems in the form of placing a location to sell products that are still not fixed and official. For this reason, researchers use STP theory, namely Segmentation, Targeting, and Positioning so that they can determine the right strategy to provide solutions to the problems faced by MSME shop owners. This type of research uses a qualitative descriptive approach, while the method in this research is qualitative by carrying out observations in the field, by visiting the relevant MSMEs directly.